A Comparative Analysis of British, American, and Australian English Accents Using Praat Software - Rangkuti, Ana Rahmawati; Syarfina, T; Widiantho, Yuri (LingPoet: Journal of Linguistics and Literary Research, 2026)
This study investigates the acoustic differences among British, American, and Australian English accents using Praat software. A descriptive quantitative method was employed, and the data were obtained from a publicly available online source providing spoken English samples of the three accents. Two English sentences were selected and analyzed to measure acoustic features, including duration, fundamental frequency, and intensity. The analysis was conducted by segmenting each sentence in Praat and recording the acoustic measurements. The results show that British English consistently has a longer duration and higher average intensity compared to American and Australian English, indicating clearer and more emphasized speech production. In contrast, Australian English exhibits the highest average fundamental frequency across all analyzed sentences, reflecting a higher pitch level. American English demonstrates moderate values in duration, frequency, and intensity. These findings confirm that British, American, and Australian English accents display distinct acoustic characteristics even when producing the same sentences, highlighting the usefulness of acoustic analysis in identifying accent differences.